Stem Cells and Cancer Stem Cells, Volume 13 Therapeutic Applications in Disease and Injury - Hayat, M.A (Stem Cells and Cancer Stem Cells, 2015)
This is the thirteenth volume in a series which presents current understanding of stem cells and cancer stem cells. This book presents many relevant topics including the different sources of cancer stem cells: the features, roles and clinical potential of stem cells emerge from engaging with this comprehensive work. Chapters explore molecular mechanisms underlying human somatic cell reprogramming to generate induced pluripotent stem cells, and provide expert discussion of the advantages and limitations of applications of some of the stem cell types (pluripotent stem cells, neural stem cells). Many advances are explored, including the importance of stem cell markers in diagnosis, the role of stem cells in angiogenesis and a method for isolating multipotent endothelial-like cells from human adipose tissue, to name a few. Readers will also find a consideration of mathematical models and other quantitative tools which could facilitate research and discovery in the field. The editor's preface to the book and the series is particularly helpful in introducing the work presented in this volume. The detailed overviews, practical experience and insights of international expert authors presented in this handbook will be of value to both professional practitioners and scholars in basic research.